A broadband active damping method for high-frequency resonance suppression in MMC-HVDC system. (March 2023) - Yang, Shiqi; Liu, Kaipei; Qin, Liang; Zhu, Shu; Xu, Bo; Wang, Qing
Highlights: High-frequency resonance is suppressed by broadband MMC impedance reshaping. Phase compensation is adopted to eliminate the negative damping of MMC. The proposed method is effective under various operating scenarios of ac grid. A controller parameter design method is presented in detail. Abstract: Negative damping in modular multilevel converter (MMC) impedance may lead to high-frequency resonance (HFR) in MMC-high-voltage direct current systems. The existing solution is based on amplitude attenuation by digital filters. However, filters have weak amplitude attenuation and obvious phase shifts in the attenuation band, resulting in the transfer of negative damping. The system still has a risk of HFR when grid condition is changed. This study proposed a broadband active damping method based on phase compensation to address this limitation. The embedding position and scheme of the phase compensation controller are optimally designed through impedance-based analysis. By tuning parameters correctly, the negative damping of MMC is eliminated over a wide frequency range (500–2000 Hz). Thus, the proposed method performs better in HFR suppressing under varying grid conditions. In addition, considering the harmonic amplification problem caused by the differential link, an inertia link and a proportional link are further employed to increase high frequency impedance magnitude. Time-domain simulations in MATLAB/SIMULINK verify the effectiveness of the proposed method.